2010
DOI: 10.1097/01.aoa.0000366982.97449.17
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia for Cesarean Delivery and Learning Disabilities in a Population-based Birth Cohort

Abstract: T he impact of obstetric anesthesia on short and long-term behavior and development of a neonate/child is not thoroughly understood. In animal studies, exposure of fetuses/neonates to anesthetics administered to the mother causes histopathologic changes in the brain; even single, relatively brief administrations may be associated with a diminished capacity to retain learned behavior and/or abnormal behaviors resembling autism. The significance of this in humans is not clear, but the authors of this study recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 42 publications
0
60
0
6
Order By: Relevance
“…This is in contrast to earlier studies finding no evidence of an association using broad-based summary scores, but in line with more recent data finding exposure to anesthesia associated with learning disability and receipt of individualized education programs for speech/language impairment. 13,15,16,19,20 Our findings may play an important role in directing future studies by identifying deficits in specific neuropsychological domains associated with anesthetic exposure. It is also noteworthy that the outcomes of language and reasoning cannot be easily assessed in the animal model, which emphasizes the importance of studies in humans.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This is in contrast to earlier studies finding no evidence of an association using broad-based summary scores, but in line with more recent data finding exposure to anesthesia associated with learning disability and receipt of individualized education programs for speech/language impairment. 13,15,16,19,20 Our findings may play an important role in directing future studies by identifying deficits in specific neuropsychological domains associated with anesthetic exposure. It is also noteworthy that the outcomes of language and reasoning cannot be easily assessed in the animal model, which emphasizes the importance of studies in humans.…”
Section: Discussionmentioning
confidence: 82%
“…In the past, outcomes such as diagnostic codes, academic performance, standardized testing, school and medical records, and parent and teacher surveys have been used. [13][14][15][16][17][18]20 Although some of these studies have found differences between exposed and unexposed children, directly administered neuropsychological assessments may have increased sensitivity to capture subtle effects that may be difficult to detect clinically. Neurodevelopmental studies of lead, pesticides, and other potential neurotoxins have similarly found that appropriate assessment tools are critical in documenting the effects of exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, slightly milder disorders were found in children whose mothers underwent regional anaesthesia for Caesarean section. The authors suggest that short-term exposure to general anaesthetics does not affect long-term neurodevelopmental disorders [38]. Another retrospective cohort study encompassed a group of 5,357 children born in the years 1976-1982.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…It was concluded in a study published by the Mayo Clinic in 2009, in which the impact of obstetric anaesthesia on learning disabilities in children aged five years and younger was assessed, that there was no evidence of harm following Caesarean and vaginal delivery. 15 A feasibility pilot study, published by a group from the Netherlands in the same year, assessed neurobehavioural development after a single incident of anaesthesia exposure before the age of six years by using a questionnaire for ages 1-14 years. The authors concluded that, taking into account the size of the study, there was no "indisputable evidence" against the use of anaesthesia in the young.…”
Section: Human Studiesmentioning
confidence: 99%